Design and Development of Search and Rescue Robot - Mohd Annuar, Khalil Azha; Md Zin, Muhammad Haikal; Harun, Mohamad Haniff; Mohd Ab Halim, Mohd Firdaus; Azahar, Arman Hadi (IJMME-IJENS, 2016)
Search and rescue robot is developed mainly to move through rubbles and debris. When a natural disaster such as an earthquake struck causing the building to collapsed, this robot can be used to search for victims and transfer to safe place. Search and rescue robot is equipped with a robotic arm to perform the evacuation process. With this robotic arm, robot can easily grab the victim in collapsed building and bring to safe place. Generally, there is a lot of robot like this used for rescue operation in collapsed building. But non of them is control by using mobile devices. So this paper is purposely designed to develop a prototype of robotic vehicle using mobile devices as controller by using Bluetooth transmission. The distance can vary from 10 meter to 100 meter depending on the type of Bluetooth module used. This robot is powered by Arduino Uno R3 board using 9V AA battery for power supply. In order to control this robot using mobile devices, an application was designed by using MIT Inventor to create an application interface between robot and mobile devices. While for the robotic arm will be design by using Autocad software. In addition, robotic arm will also use four servos to move.